Molecular diagnostic platforms for point-of-need pathogen detection - Jain, Sidhartha, author; Henry, Charles S., advisor; Geiss, Brian J., advisor; Dandy, David S., committee member; Magzamen, Sheryl L., committee member (Colorado State University. Libraries, 2021)
Rapid, accurate, reliable nucleic acid testing (NAT) platforms are essential in the diagnosis and management of diseases. The inherent complexity associated with NAT requires that such testing be performed in centralized laboratories by highly trained personnel. Modified molecular technologies that can be used at the point-of-care (POC) are needed to improve the turnaround times of results and lower the global burden of infectious diseases. To help address this urgent need, we have developed a nucleic acid sensor platform utilizing nuclease protection and lateral flow detection for rapid, point-of-need nucleic acid analysis. We have also improved the analytical performance of the assay by pairing it with isothermal padlock rolling circle amplification (RCA). RCA is one of the simplest and most versatile isothermal amplification techniques as it only requires one primer and a strand-displacing polymerase. Utilizing our rolling circle amplification lateral flow platform, we have developed assays for beta-lactamase resistance genes for antimicrobial resistance monitoring and severe acute respiratory virus coronavirus 2 (SARS-CoV-2). We have also explored the use of exponential isothermal amplification to further improve the assay limit of detection. We also propose a microfluidic device to rapidly detect the RCA amplicons. The device allows programmable sequential delivery of reagents to a detection region, reducing the number of user steps. With further development, such microfluidic devices can be used to develop fully integrated sample-to-result molecular diagnostic platforms that integrate sample pretreatment, amplification, and detection in an easy-to-use, point-of-need nucleic acid sensor platform. Chapter 1 presents a brief review of the nucleic acid testing landscape, the challenges associated with the development of point-of-need nucleic acid sensors and recent successes utilizing paper-based devices for fully integrated sample-to-result sensors. Chapters 2 and 3 discuss the development of the nuclease protection lateral flow assay and padlock probe-based rolling circle amplification lateral flow assay. Chapter 4 describes our work on the use of exponential RCA to improve the limit of detection of the SARS-CoV-2 assay. In Chapter 5, we present our work on a paper-plastic microfluidic device for the rapid detection of the RCA amplicon. We believe that such devices can be used for the development of integrated molecular diagnostic sensor platforms that can be used at the point-of-need in resource-limited settings.
Keywords: nucleic acid testing; rolling circle amplification; pathogen detection; molecular diagnostics